PENGARUH VARIASI TEGANGAN TABUNG PADA INFORMASI ANATOMI RADIOGRAFI CRANIUM PROYEKSI LATERAL DENGAN MENGGUNAKAN PROCESSING DIGITAL RADIOGRAPHY - nurul auliyaa hasbi; Datu Euphratadhi Pradana; Wahdini Hanifah (Journal of Hospital Administration and Management (JHAM), 2026)
Almost all hospitals use radiology aircraft that have an automatic exposure factor system, including in the regulation of tube voltage. However, the value of the automatic exposure factor is not adjusted to the patient's condition or the thickness of the object. Since the tension linkage of the tube does not correspond to the thickness of the object, research must be carried out to optimize the tension value of the tube according to the anatomical data collected. This study aimed to determine how the variation in tube tension affects the anatomical information on lateral projection cranium radiography. Knowing the value of the tube voltage used to best show anatomical information, radiography, radiography, cranium, lateral projection, and relationship to each other. The place this research is RSKD Dadi, Makassar. This research was carried out through a quantitative method with an experimental approach. The research tool collected data through observation and questionnaires. Radiography results of lateral projection cranium examination with kV variation. Data analysis was carried out using the SPSS test. The results showed that the ideal tube voltage value to use was 75 kV, with the highest average values of 7.63, 6.00 for 80 kV and 4.72 for 85 kV. The test results showed that the three cranial radiographies had different qualities. The significance value is 0.000 less than 0.05. The use of good tube voltage to use based on the questionnaire is 75 kV, because it can show the quality of clear anatomical details so that it is easy to analyze.